2015
DOI: 10.1590/1807-3107bor-2015.vol29.0018
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity factors of temporomandibular disorders: a critical review of the literature

Abstract: Facial pain often persists long after any identifiable organic pathology has healed. Moreover, in a subgroup of patients with temporomandibular disorder (TMD), no treatment is effective. Knowledge of factors associated with persistent pain in TMD could help identify personalized treatment approaches. Therefore, we conducted a critical review of the literature for the period from January 2000 to December 2013 to identify factors related to TMD development and persistence. The literature findings showed that chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
0
11
0
3
Order By: Relevance
“…Researchers have proposed several psychological factors related to TMD development and maintenance, such as fear of pain, coping, catastrophizing, fear of movement, depression, stress, somatization and anxiety,8 which is why the psychological component should always be considered. Psychological therapy should be included in the classical biomedical treatment modalities of this group of patients to improve outcomes 9.…”
Section: Main Evidence-based Treatmentsmentioning
confidence: 99%
“…Researchers have proposed several psychological factors related to TMD development and maintenance, such as fear of pain, coping, catastrophizing, fear of movement, depression, stress, somatization and anxiety,8 which is why the psychological component should always be considered. Psychological therapy should be included in the classical biomedical treatment modalities of this group of patients to improve outcomes 9.…”
Section: Main Evidence-based Treatmentsmentioning
confidence: 99%
“…Por otro lado, también se menciona, una relación positiva vinculada a la presencia de ansiedad y/o depresión en relación con el dolor en estos pacientes. Se piensa que el papel de las interacciones entre los factores biológicos y psicológicos en la génesis del dolor orofacial es complejo, ya que actúan como neuro-moduladores que pueden aumentar el estímulo responsable el dolor agudo empeorando, el pronóstico y favoreciendo la cronificación del mismo, especialmente cuando existe un componente miofascial asociado a la DTM 19,21,22 .…”
Section: Discussionunclassified
“…La limitación en la apertura, los ruidos articulares y el componente miofascial se pueden relacionar con la discapacidad funcional vinculada a la DTM crónica. En la literatura se recoge el papel destacado de las comorbilidades en el desarrollo y mantenimiento de esta alteración funcional 1,13,21,24 . Se describe cómo la migraña y la fibromialgia aumentan la limitación y el deterioro funcional afectando a los movimientos mandibulares y a la apertura oral, favoreciendo la rigidez y la fatiga que repercute negativamente en funciones básicas como la masticación y fonación 11,17,18 .…”
Section: Discussionunclassified
“…Currently it is known that parafunctional habits and psychosocial factors (e.g., anxiety, depression and fatigue) play an important role in the development of TMD 6,7 . Thus, treatments approaching only biomedical factors are considered insufficient to promote long-term improvement of TMD 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a biopsychosocial approach, that offers equal emphasis to the treatment of physiologic, psychological and social factors can result in substantial improvements in TMD pain 8,9 . Therefore, approaches involving self-care and behavioral therapies, including education about the condition, associated with self-care as heat packs, jaw exercises, and strategies aiming to reduce the parafunctional jaw activities and muscular relaxation 10 .…”
Section: Introductionmentioning
confidence: 99%